In Search of Liberation: Transcendentalist Literature and the Future of American Work - Cohen, Sarah R. (Tufts Archival Research Center, 2022)
This thesis explores one of the social issues critiqued by the authors and reformers known as the American Transcendentalists: the conditions of work. The central goal of my thesis is to engage with Transcendental texts to reimagine work in today’s late-capitalist society. I argue that the Transcendentalists' reactions pave the way for a new way to understand America's contemporary relationship to work, as this movement offers surprisingly relevant suggestions for both personal relationships to work and, more generally, to an American workforce that is continuing to experience the shocks of a global pandemic.; Thesis (B.A.)--Tufts University, 2022.; Submitted to the Dept. of English.; Advisor: Nate Wolff.